Sustainable Entrepreneurship: A Family Self-Employment Economic Development Model - Fauziah, Dien Ajeng; Khoir, Fatihul; Sa'adah, Ummi; Prastyo, Dimas Hadi; Hermanto, Bambang Agoes; Lestari, L. Tri (Atestasi : Jurnal Ilmiah Akuntansi, 2025)
Purpose: This study aims to explore sustainable entrepreneurship as a transformative paradigm that integrates economic growth with environmental and social responsibility. Specifically, it investigates the role of family self-employment in promoting sustainable economic development at the community level. Research Design and Methodology: This study employed a qualitative case study approach, collecting data through semi-structured interviews and focus group discussions with family business owners in Geluran Village, Sidoarjo Regency, Indonesia. The Resource-Based View (RBV) theory guided the study in analyzing how internal family resources support sustainability. Findings and Discussion: The findings reveal that family self-employment strategically drives sustainable entrepreneurship by fostering resilience, long-term orientation, and ethical business practices. Family businesses are shown to implement sustainability models such as the Triple Bottom Line, circular economy principles, and collaborative networks. Despite their strengths, the heterogeneity of family businesses poses challenges for generalization, indicating the need for more context-specific studies. Implications: This research provides practical and policy-level implications by highlighting the potential of family-run enterprises to achieve inclusive and sustainable development. It suggests that targeted support through financial access, capacity-building, and sustainability programs is essential to enhance the contribution of family businesses to long-term economic and social well-being.